Analisis Empiris Transaksi Non-Tunai Dan Variabel Ekonomi Terhadap Dinamika Pengganda Uang Di Indonesia - Mahendra, Weri; Kusuma Tegar, Brian; Affandi, Akhsyim (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2024)
This research was conducted to analyze the effect of non-cash instruments, namely debit card transactions, credit card transactions, electronic money, and economic variables, namely interest rates and inflation on the money multiplier in Indonesia. The data analysis technique uses the Error Correlation Model via Eviews 9. The tests carried out are the stationarity test, cointegration test, and ECM model estimation. This study uses quantitative data types for 2012-2021 with a total of 120 observations. Data is sourced from the website of Bank Indonesia and the Central Bureau of Statistics (BPS). The results of the study show that debit transactions have no significant effect on the money multiplier in the short term. Meanwhile, in the long term, debit transactions have a positive and significant effect on the money multiplier number. Credit transactions have a significant negative effect on the short-term and long-term money multiplier numbers. Electronic Money and inflation show no significant effect in the long term or short term on the money multiplier number. Interest rates show a negative and significant effect on the money multiplier in the short term. Meanwhile, in the long run, interest rates do not have a significant effect on the money multiplier in Indonesia. The implication of the study is the need to encourage the use of debit transactions through education, infrastructure, and incentives, as well as stricter supervision and policies in granting credit given its negative effect on the money multiplier.